2021
DOI: 10.1161/circep.120.008817
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cell Selectivity of Reversible and Irreversible

Abstract: Background - Pulmonary vein isolation (PVI) is a common catheter ablation technique used to treat atrial fibrillation originating from the pulmonary veins. However, incomplete lesion formation, pulmonary vein reconnection, and collateral damage to the phrenic nerve and esophagus can occur. Electroporation is a new modality to ablate and has the potential for permanent PVI and selective efficacy on cardiac tissue, however strong evidence of selective myocardial injury using electroporation is lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…One of the bottlenecks of electroporation is that its protocol, especially the parameters of the applied electric pulses (amplitude, duration, number, repetition rate), needs to be optimized for each specific application and also for each specific cell/tissue type ( Cemazar et al, 2009 ; Rols and Teissié, 1998 ; Hunter et al, 2021 ). When using electroporation for intracellular delivery of nucleic acids, the cells need to survive the treatment to be able to express the transgene.…”
Section: Introductionmentioning
confidence: 99%
“…One of the bottlenecks of electroporation is that its protocol, especially the parameters of the applied electric pulses (amplitude, duration, number, repetition rate), needs to be optimized for each specific application and also for each specific cell/tissue type ( Cemazar et al, 2009 ; Rols and Teissié, 1998 ; Hunter et al, 2021 ). When using electroporation for intracellular delivery of nucleic acids, the cells need to survive the treatment to be able to express the transgene.…”
Section: Introductionmentioning
confidence: 99%
“…The data presented here showing the similar susceptibility of neurons and cardiac cells are in contrast with previous works. A recent study by Hunter et al reported that rat ventricular cardiomyocytes had more susceptibility to damage for a given field strength in contrast to cortical neurons post electroporation [14]. The difference in our study is that we used neuronal lines that are more representative of the peripheral nervous system, suggesting a possible tissue selectivity to cell injury after electroporation.…”
Section: Discussionmentioning
confidence: 90%
“…The difference in our study is that we used neuronal lines that are more representative of the peripheral nervous system, suggesting a possible tissue selectivity to cell injury after electroporation. Furthermore, in our study, HL-1 cells were extracted from adult mouse atrial cardiomyocytes in comparison to neonatal rat ventricular myocytes (NRVM) used by others [14]. In addition, immature H9C2 cardiac cells in the Kaminska et al study showed that electric field intensities of above 375 V/cm of five pulses of shorter 50 µs could cause 80% cell death [13].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A scan of the potential range of field strengths that might induce cell death is required and would be enhanced by the addition of threshold data on neuronal, cardiomyocyte and fat tissue found in the heart. Very recently, Hunter et al showed that cardiac cells are more susceptible to electroporation damage than cortical neurons and oesophageal smooth muscle cells [ 75 ]. However, there are very few reports of this nature examining the different IRE thresholds of cardiac cells relative to other appropriate cardiac–neuronal model systems.…”
Section: Electroporation As An Ablative Approachmentioning
confidence: 99%